2018
DOI: 10.1002/jsfa.9431
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba sarcotesta polysaccharide inhibits inflammatory responses through suppressing both NF‐κB and MAPK signaling pathway

Abstract: BACKGROUND: Polysaccharides, common components of natural products extensively studied as dietary supplements and functional foods, have been found to have various activities. In the present study, a water-soluble polysaccharide, namely GBSP3a, was isolated and purified from G. biloba sarcotesta. The anti-inflammatory activity of GBSP3a in lipopolysaccharide (LPS)-induced RAW264.7 macrophages and the potential underlying molecular mechanisms were then assessed. RESULTS: GBSP3a exerted its anti-inflammatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…a‐c). There have been several reports about the anti‐inflammatory ability of polysaccharides, like Lentinula edodes and Ginkgo biloba . And strikingly, most researches proposed the essential role of the immune system in the anti‐inflammatory process including Dioscorea opposita .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a‐c). There have been several reports about the anti‐inflammatory ability of polysaccharides, like Lentinula edodes and Ginkgo biloba . And strikingly, most researches proposed the essential role of the immune system in the anti‐inflammatory process including Dioscorea opposita .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports about the anti‐inflammatory ability of polysaccharides, like Lentinula edodes and Ginkgo biloba . And strikingly, most researches proposed the essential role of the immune system in the anti‐inflammatory process including Dioscorea opposita . Severe inflammatory symptoms were below detection after CP treatment such as inflammatory cell infiltration, which indicated the possibility of its impact on the immune cells in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-neuroinflammatory activity of Ginkgo biloba is due to its ability to hinder the discharge of pro-inflammatory cytokines and the stimulation of MAPKs signalling (J. Ye et al, 2019). Further study shows that neuroprotective effects of GbE is because of its positive action on Akt signalling which leads to anti-apoptotic acticity (Yu et al, 2018) J. Withania somnifera : Withanolides, withanine, somniferine, somnine, somniferinine, withananine, psuedo-withanine, are the chief constituents obtain from Withania somnifera (Ws), belonging to family Solanaceae (Dafni & Yaniv, 1994;Kulkarni & Dhir, 2008).…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…Purified polysaccharide extracted from Apios americana Medikus tuber suppressed the release of NO and inflammatory cytokines from LPS-induced RAW 264.7 cells . Ginkgo biloba sarcotesta polysaccharide has been reported that it could inhibit the secretion of NO in LPS-stimulated RAW264.7 macrophages (Ye et al, 2018).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%